Penerapan Metode Diskusi Dalam Mata Pelajaran Pendidikan Agama Islam Untuk Meningkatkan Hasil Belajar Siswa di SMA Negeri 1 Airpura - Jasril, Jasril (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to explore the impact of applying a learning model based on cognitive, constructivist, and social cognitive theories on student learning outcomes. The research was conducted in two cycles, each involving planning, action, observation, and reflection. The results of Cycle I showed improvement, despite facing some challenges in the implementation. In Cycle II, the improvements made led to a more significant increase in students’ cognitive and affective abilities. Learning based on social interaction and collaborative problem-solving proved to increase student engagement and strengthen their understanding of the material. This study concludes that the application of constructivist and social cognitive learning models is effective in enhancing students’ learning outcomes.